Generic strategic profiling of entrepreneurial SMEs – environmentalism as hygiene factor - Marc Dressler (International Entrepreneurship and Management Journal, 2022)
Climate change, extreme weather phenomena, droughts, fires etc. are just few examples of man-induced impact, jeopardizing the future of mankind. Businesses are increasingly held responsible for and try to manage their environmental impact. Environmentalism and lately sustainability (manifesting an equal pursuit of environmental, social, and economic goals) guide strategic orientation. Whereas large corporations anchor environmentalism in their mission statements and strategic positioning, the strategic reflection of sustainability and especially environmentalism in the business models of small enterprises is less researched. Their entrepreneurship builds on exploiting environmental opportunities and is deemed characteristic for small enterprises, but a lower penetration of strategic instruments paired with a predominant opportunistic behaviour seem to characterize SMEs strategic environmentalism. In order to examine the entrepreneurial environmentalism and the strategic value for SMEs an empiric study leaned on population ecology. An online survey with 291 small enterprises explored environmentalism, strategic profiling, and performance impact in an agricultural and entrepreneurial industry. Study results manifest a positive performance impact of sustainability-oriented and thereby ecologic environmentalism. Ecologic environmental consciousness has been identified for all generic strategic groupings but it separates into two distinctive clusters, one with a process and one driven by market focus. Foremost, eco-centric strategic measures were identified as core levers to increase product quality – a promising finding that secures further strategic ecological environmentalism.
Keywords: 650; Entrepreneurship; Strategic management; Environmentalism; Population ecology; Sustainability; Ecological strategy; Innovation; Generic strategies; Strategic grouping; Wine industry; Success factors